TECHNOLOGY FOR RECOVERY OF STEEL PIPE SUPPLY SYSTEMS - and and (Municipal economy of cities. Series: «Economy science», 2013)
The condition of the steel pipes of water supply. Are the main methods of recovery after injury. Shows one of the most progressive methods of recovery of the pipeline by pulling the pipe sections of plastic tubing.